(untitled) (Biological Sciences - PJSIR, 1999)
Twenty one seed-borne fungi were recorded from 196 seed samples collected from seeds used for sowing of sun-flower crop and a total of ten field diseases wererecordedduring surveyof sunflowercrop in 199I-92. All the field diseases observed inthis surveyareknowntobe seedtransmitted.Thecausal organisms offive field diseases namely Alternaria leaf spot, charcoal rot, head rot, Phoma leaf spotlblack stem rot and Phomospsis leaf spot were found to be associated with seeds. In germination test, it was found that role of seed-borne fungi in causation of various abnormalities in germinationdepended onthe frequencyof theiroccurrence inthe seeds.